Education in prosthetic and orthotic training: Looking back 50 years and moving forward. (December 2020) - Spaulding, Susan Ewers; Kheng, Sisary; Kapp, Susan; Harte, Carson
There is a long history of prosthetic and orthotic services helping to mitigate the impact of physical impairment by restoring function, and enabling and equipping the user. The training of health professionals who design, fit, and maintain prosthetic and orthotic devices has evolved over the centuries, reflecting an increase in knowledge, technology, understanding, and social attitudes in each era. Improvements in pedagogical thinking and biomechanical understanding, as well as the advent of new integrated technologies, have driven the profession over the past 50 years to modernize, evolve training and service delivery models in line with new attitudes toward clients, and search for new ways to improve users' quality of life. In this narrative review, the authors examined the evolution of prosthetic and orthotic education, the impact of changing educational techniques and technologies, and the impact of the International Society for Prosthetics and Orthotics in that process. Through conversations with experts and review of peer-reviewed literature, accreditation documents, and the International Society for Prosthetics and Orthotics records and databases, the authors identified three areas of change in prosthetics and orthotics education over the past 50 years: (1) prosthetic/orthotic curriculum content, (2) pedagogy and course delivery, and (3) internships/residencies. This narrative review is a snapshot of a growing profession and we can only speculate where the next 50 years will lead us as we strive to serve patients, ever placing their needs and aspirations at the center of this professional service.